A Layered Description of a Premixed Flame Stabilized in Stagnating Turbulence. Issue 9 (1st September 2016) - Mura, Arnaud; Robin, Vincent; Kha, Kim Q. N.; Champion, Michel
ABSTRACT: In the thin-flame regime of turbulent premixed combustion, instantaneous progress variable gradients are essentially fixed by propagating flamelets. The laminar flamelet internal structure thus imposes, at least to some extent, the progress variable one-point one-time statistics, i.e., the progress variable PDF . In the present study a generalized presumed probability density function (PDF) shape is considered to account for possible departures from the thin-flame limit. The parameters that characterize this PDF shape depend on the ratio of the Kolmogorov length scale to laminar flame width. The corresponding framework may be associated to a layered description of the turbulent flame brush (TFB) with the thicknesses of the different sub-layers determined from the knowledge of both the Reynolds and Karlovitz numbers, ReT and Ka . It incorporates boundary layers on both sides of the TFB, which are associated to the finite thickness of the local flamelets, i.e., small but finite values of the Karlovitz number. This description leads to a modeling proposal for premixed turbulent combustion. A tabulation is constructed based on canonical one-dimensional planar unstrained laminar premixed flame computations and the different quantities are tabulated as functions of ReT and Ka . The final closure is applied to the numerical simulations of premixed flames stabilized in stagnating turbulence.